Identification of biosurfactant-producing fungi isolated from the Costa Rican mangrove - Valerio-Aguilar, Kenneth; Fallas-Mendez, Adriana; Rodríguez-Rodríguez, Jorengeth; Singh Thakur, Samrendra; Solano-González, Stefany (Uniciencia, 2026)
In Costa Rica, mangrove potential has not been studied from a biotechnological perspective, despite reports from other latitudes of promising fungi associated with these ecosystems, including biosurfactant potential. These molecules are primarily used in industry as emulsifiers; however, studies indicate their potential in healthcare, pharmaceutical, and agricultural applications. [Objective] This study aimed to screen and preliminarily identify fungal strains capable of producing biosurfactants by implementing a set of effective, low-cost, straightforward assays for future exploitation. [Methodology] Five fungal strains from the Manuel Antonio mangrove in Puntarenas, Costa Rica, were isolated, molecularly identified, and assessed for biosurfactant production utilizing the crude biosurfactant broth. The drop collapse test, oil displacement test, emulsification index, and hemolysis tests were assessed. [Results] The use of crude biosurfactant broth minimized the cost and time required for purifications, which enabled the reduction of screening time for all fermentations. Isolate MP4 displayed, overall and consistently, better performance than the other strains evaluated for growth and biosurfactant production assays, especially for the emulsification index and blood hemolysis test. ITS and LSU molecular markers were analyzed, and MP4 was taxonomically assigned as Trichoderma sp.; however, it was shown to be closely related to T. melanomagnum. [Conclusions] Results emphasize the unexplored potential of mangrove resources in Costa Rica for biosurfactant production, and although preliminary, they demonstrate the value of conducting future comprehensive studies to evaluate this fungal potential.